Improving Learning Outcomes by Using Think Pair Share (TPS) Cooperative Learning Model at Primary School Students - Zuddin, Mufari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
This classroom action research was conducted to improve the learning outcomes of Civics by applying the cooperative model of Think Pair Share (TPS) type on V grade students that consists of 24 students. Improving PKN learning outcomes by applying cooperative learning model Think Pair Share (TPS). Factors that led to the improvement of Civics learning outcomes with the application of Think Pair Share (TPS) Student Class V SDN 003 Bangkinang. The research subjects of Grade V students are 24 students. The result of the research is the improvement of learning result before the action is done to cycle I and II. Before the students' learning outcomes were classified as